The Effect of Financial Literacy, Lifestyle, and Social Media on Student Consumptive Behavior - Jenanu, Jularia Ilsa; Andayani , Endah; Naim , Naim (International Journal of Business, Law, and Education, 2025)
The purpose of this study is to determine the impact of financial knowledge, lifestyle and social media on student consumption behaviors for economic education at PGRI Kanjuruhan University Malang. This study uses a quantitative approach with sample pickup technology, with 53 students, with sample pickup. The results showed that financial capacity in part had no significant impact on consumption behavior, lifestyle had a significant impact on consumption behavior, and social media had a significant impact on consumption behavior. At the same time, financial competence, lifestyle and social media have a major impact on student consumption. Based on these results, we can draw conclusions